SNMMI Procedure Standard/EANM Practice Guideline for Fibroblast Activation Protein (FAP) PET - Hope, Thomas A.; Calais, Jeremie; Goenka, Ajit H.; Haberkorn, Uwe; Konijnenberg, Mark; McConathy, Jonathan; Oprea-Lager, Daniela E.; Trimnal, Laura; Zan, Elcin; Herrmann, Ken; Deroose, Christophe M. (Journal of nuclear medicine, 2025)
The Society of Nuclear Medicine and Molecular Imaging (SNMMI) is an international scientific and professional organization founded in 1954 to promote the science, technology, and practical application of nuclear medicine. The European Association of Nuclear Medicine (EANM) is a professional non-